Rapid bulk endocytosis and its kinetics of fission pore closure at a central synapse - Wu, Wei (National Academy of Sciences, 2007)
Upon exocytosis, fused vesicles must be retrieved for recycling. One route of retrieval is to generate endosome-like structures, from which small vesicles bud off. Endosome-like structures are widely thought to be generated slowly (≈1 min) from the plasma membrane, a process called bulk endocytosis. Although the concept of bulk endocytosis seems established, the kinetic evidence showing the instant of the bulk membrane fission at synapses is still missing. The present work provides this missing piece of evidence at a calyx-type synapse. We used the capacitance measurement technique, which offers a high time resolution (≈1 ms) to resolve the fission process. The instant of bulk membrane fission was reflected as a brief downward capacitance shift (DCS) of ≈20–500 fF (mean = 123 fF) with 10–90% decay time of ≈30–500 ms. At least 8.6–11.0% of exocytosed vesicles were retrieved by DCSs. During a DCS, the decrease in the fission pore conductance was detected, from which we found that the fission pore diameter decreased at ≈39 nm/s. This provided the measurement of the rate of fission during bulk endocytosis at synapses. The DCS frequency peaked (≈0.021 Hz) in <10 s after stimulation and decayed with a half time <20 s, indicating that the time course of bulk endocytosis is much faster than previously estimated with low time-resolution techniques. Our results also suggest that bulk endocytosis was composed of two kinetically different steps: the DCS that reflected the fission process and the time between stimulation and the DCS, during which membrane invagination led to the fission pore formation.